Labour and the Commemorative Landscape in Industrial Cape Breton, 1922-2013 - MacKinnon, Lachlan (Material Culture Review, 2013)
Abstract Labour landmarks are monuments, memorials, plaques and other sites that commemorate the past experiences of workers in society. These sites are also manifestations of the collective memory of labourers. In industrial Cape Breton, which has a long history of labour and class struggle, an analytical survey of labour landmarks reveals how the industrial past has been remembered and memorialized. This overview reflects the narratives that have been attached to these sites, the ways in which historical memory has been localized and constructed in industrial Cape Breton, and the new layers of meaning that are revealed as these communities transition into post-industrialism.